Respiratory sinus arrhythmia and heart period in infancy as correlates of later oppositional defiant and callous-unemotional behaviors. (January 2017) - Wagner, Nicholas; Mills-Koonce, Roger; Willoughby, Michael; Propper, Cathi; Rehder, Peter; Gueron-Sela, Noa
Extant literature suggests that oppositional defiant disorder (ODD) and callous-unemotional (CU) behaviors in childhood and adolescence are associated with distinct patterns of psychophysiological functioning, and that individual differences in these patterns have implications for developmental pathways to disorder. Very little is known about the associations between psychophysiological functioning in infancy and later ODD and CU behaviors. This study examined associations between basal autonomic nervous system (ANS) functioning in infancy and ODD and CU behaviors in later childhood. Using longitudinal heart period (HP) and respiratory sinus arrhythmia (RSA) data from the Durham Child Health and Development Study ( N = 206), the current study tested associations within a structural equation modeling framework, between continuous measures of HP and RSA across the first 2 years of life, and later ODD and CU behaviors at first grade. Results indicate that ODD and CU behaviors in childhood are associated with lower baseline RSA, but not HP, across infancy. The implications of these findings for developmental models of ODD and CU behaviors are discussed.